Applying the 20.1 Sub-Clause of the Fidic Conditions of Contract under Standards of Polish Civil Law - Jaworski, Bartłomiej (University of Wroclaw. Faculty of Law, Administration & Economics, 2017)
FIDIC conditions of contract are patterns of contractual agreements for project or construction works widely used in the world. They were designed to facilitate the implementation of construction investment for all participants. The construction practice of many countries of the world (including Poland) uses those commonly recognized international standards, although their legal nature differs in each country which uses them and it is often hard to determine the place of the FIDIC conditions of contract in national legal systems. This problem also applies to our country because the norms of civil law in accordance with the directly expressed principle of freedom of contracts allows the introduction of the FIDIC conditions of contract into agreements to perform design or construction works, but there is still a problem of some FIDIC provisions being inconsistent with the standards of the Polish civil law. An example of such incorporation of FIDIC conditions of contract causing doubts of interpretation as to their compliance with the standards of Polish law can be the 20.1 FIDIC Sub-Clause discussed in this article. This regulation seems to contain provisions inconsistent with the standards of the Polish Civil Code. It seems that this regulation contains provisions inconsistent with the norms of the Polish Civil Code, whose possible legal consequences should be looked at more closely and to trace the case law of Polish courts in this regard. It can be said that the FIDIC conditions of contract are extralegal standards functioning in the legal order without the mediation of a reference standard. They are peculiar standards-patterns with a prenormative nature and which, although indirectly, are valid do not exist in the Polish legal order through legal norms. The significant conclusion results from the article considerations - the FIDIC conditions of contract, due to their not exactly specified legal nature, take effect only to the extent that it does not conflict with national standards.
Keywords: FIDIC; charakter prawny warunków kontraktowych FIDIC; warunki kontraktowe FIDIC; roboty budowlane; normy prawne polskiego prawa cywilnego